Analysis of Household Daily Water Consumption Dynamics in the Tropical Environment - Timothy O. Ogunbode; Victor O. Oyebamiji; Olumide A. Oluwole; John A. Akande (Scientifica, 2023)
Understanding daily water use determinants is critical to sustainable water access and its efficient use at household level. To pursue this objective, primary data were generated through a survey of 276 respondents across the 5 quarters into which the city of Iwo is divided. 67.5% of the respondents were between 19 and 45 years old while 35.5% were between 46 and 65 years old and the remaining 3.9% comprised of those above 65 years. The results of factor analysis (FA) showed that 12 of the 40 factors analyzed were significant determinants of daily water use in homes. The 12 factors explained 85.794% of the observed variation in household daily water use. The factors in descending order were (i) closeness to water source; (ii) night time baths; (iii) household cooking; (iv) Sunday activities; (v) water demands of the dry season; (vi) morning time water use; (vii) household size; (viii) respondents’ attitude; (ix) water availability in the dry season; (x) break in water flow; (xi) social events; and (xii) source of water. Further evaluation condensed the results into four categories, namely, (i) season-associated information; (ii) household-related information; (iii) time of the day; and (iv) water source-related information. The result of correlation analysis showed weak associations among 83.33% of the variables, indicating that each variable should be treated separately from others in the matter relating to daily variation in home water use. The study concluded that household-related information and time of the day (contributing 62.02% of the absolute explanation) are most significant to daily variation in water use at the household level and should be considered when prioritizing effective policies for water use and management.